Nilai-Nilai Asas Pemilihan Umum dalam Islam - Mita Fitria (STAI YAPTIP Simpang Empat Pasaman Barat Indonesia in collaboration with International Islamic Studies Development and Research Center (IISDRC), 2022)
The intent and purpose of conducting this research is to understand how the principles of general elections, abbreviated as elections in Indonesia, are in accordance with Islamic teachings or values ​​or not and how their implementation in the field is fully in accordance with existing values ​​or in accordance with the hope that has been stated in the principles of general elections. This research is a form of library research as well as field or field research which is qualitative in nature and uses descriptive methods. As for the primary data, namely the public, books, articles about democracy or elections, as well as phenomena that exist in the field or that occur. The results found in the research on the principles of assessment are: the principles of elections are in accordance with existing Islamic values, be it direct, general, free, honest, secret, fair, then for implementation in the field there are still incompatible values which apply to implementation in the field, for example there is party verification that is not in accordance with regulations, the occurrence of money politics carried out by unscrupulous election organizers so that it becomes an election matter.